2002
DOI: 10.1023/a:1015081822336
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To evaluate the role of endogenous opioids in regulation of upper gastrointestinal motility in unanesthetized dogs and to differentiate the actions on mu- and delta-opioid receptors, seven strain gauges and five platinum electrodes were chronically implanted at the serosa along the antrum and duodenum and connected to a plug in the neck of the dog. Signals were processed by a Hellige AC amplifier, a rectilinear recorder, and a data aquisition system. A motility index (MI) was calculated and together with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Many previous studies have investigated the effect of opioids, especially µ-opioid agonists, on small intestinal and colonic function, but there have been few studies of the effects of δ-opioids on stomach motility. Holle and Steinbach demonstrated that a δ-opioid receptor antagonist, ICI 174 864, increases antral motility in the postprandial state in conscious dogs ( 30 ). In addition, Ruckebusch et al demonstrated that D-AIa 2 -MetS-enkephalinamide (DAMA) and D-Ala 2 -D-LeuS-enkephalin (DADLE), which are mixed µ and δ-opioid agonists, inhibit the motility of the reticulum in sheep ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have investigated the effect of opioids, especially µ-opioid agonists, on small intestinal and colonic function, but there have been few studies of the effects of δ-opioids on stomach motility. Holle and Steinbach demonstrated that a δ-opioid receptor antagonist, ICI 174 864, increases antral motility in the postprandial state in conscious dogs ( 30 ). In addition, Ruckebusch et al demonstrated that D-AIa 2 -MetS-enkephalinamide (DAMA) and D-Ala 2 -D-LeuS-enkephalin (DADLE), which are mixed µ and δ-opioid agonists, inhibit the motility of the reticulum in sheep ( 13 ).…”
Section: Discussionmentioning
confidence: 99%